Prostate Biopsies - A Retrospective Review From the University Malaya Medical Center - Dublin, N. (Malaysian Medical Association, 2003)
Prostate cancer is not common in south-east asia and in particular there are only scarce reports on the characteristics of Malaysian men with prostate cancer. A retrospective study where all prostate specimens sent to the pathology department during the period 1st January 1996 to 30th June 1998 were reviewed. A total of 131 prostate specimens were reviewed and these consisted of prostatectomy specimens, transurethral resection specimens and trucut biopsy specimens. Only 114 patients’ case notes were evaluated. Data reviewed were age, race, presenting symptoms, clinical findings and prostate-specific antigen (PSA) level. Overall incidence of carcinoma of the prostate was 19.0%. The incidence of carcinoma of the prostate with serum prostate-specific antigen (PSA) of 4.1 to 20.0 ng/ml was only 10% and 60.5% of patients had evidence of subclinical histological prostatitis. The mean age of men with carcinoma of the prostate was 71.3 years and there was no differences in the incidence of carcinoma of the prostate among the 3 major ethnic groups (Malays, Chinese and Indian). About three-quarter of the patients with carcinoma of the prostate presented with lower urinary tract symptoms, a third had haematuria and about a tenth of patients presented with urinary retention. The majority of patients presented with metastatic disease (66.7%) with a mean PSA of 1476.8 ng/ml. A significant proportion of men with prostatic diseases attending the University of Malaya Medical Center had prostate cancer (19.0%). A small proportion of men with serum PSA in the range of 4.1 to 20.0 ng/ml had prostate cancer and this is thought to be due to the background histological prostatitis. The majority of patients presented late.